2017
DOI: 10.1017/s1352465816000655
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of behavioural management principles amongst specialist paediatric dental practitioners in the United Kingdom

Abstract: Knowledge of behavioural principles amongst paediatric dentists in the United Kingdom is poor, despite their widespread reported use of such techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In most studies, the most commonly employed technique to obtain the child’s cooperation is “tell-show-do” [ 30 , 58 , 59 , 60 , 61 ], as used in the present research, followed by the positive reinforcement technique [ 59 , 60 , 62 ], also used by the trained professional who attended the children. Other authors point to distraction techniques (73%) as the second most used technique [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, the most commonly employed technique to obtain the child’s cooperation is “tell-show-do” [ 30 , 58 , 59 , 60 , 61 ], as used in the present research, followed by the positive reinforcement technique [ 59 , 60 , 62 ], also used by the trained professional who attended the children. Other authors point to distraction techniques (73%) as the second most used technique [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…There-fore, knowledge of several techniques, to be individually selected as appropriate for a particular patient, are advised for pediatric dentists. 3,19 However, Coxon et al 20 reported that pediatric dentists do feel that they have limited control and knowledge of nonpharmacological behavior guidance and dental fear. As these studies inform of limited successcontrol and knowledge of behavior guidance and pain control, the present study aims to explore the effectiveness of an educational intervention, the PaFein teaching model, for training dentists to provide pain-free local anesthesia for children.…”
Section: Discussionmentioning
confidence: 99%
“…The RNLD can advocate for adapted communication, 28 behaviour management approaches, 18,29 how an individual reports pain, 21 reasonable adjustments, ability for the patient to consent, and realistic care plan expectations 30 including perceived need for sedation. 13,18 Rada et al 18 suggest success in dental case management of the person with a learning disability can be achieved if the nurse liaises between support staff in the residential setting and the dental team.…”
Section: Discussionmentioning
confidence: 99%
“…17,32 Recommendations Many of the research papers called for further investigation into why oral care is either overlooked, or why individuals are resistant to the process of daily oral care within community learning disabilities settings. 9 This author found a paucity of existing research which considered the cross-sectional impact of a learning disability alongside an autistic spectrum condition, 24,33 sensory processing disorder, 30,18 behaviour that challenges care services 29,18 or a mental health condition 7,14 which may necessitate being in inpatient or offending behaviour settings, 8,34 and the possibility of resulting homelessness. 35 Consideration of these additional challenges in addition to a learning disability should be considered in future collaborative studies, which should include dental, nursing and care staff who work in this diverse range of settings.…”
Section: Methodsmentioning
confidence: 99%